The Invisible 'Antifa-Ost'. The Struggles of Anti-Hegemonic Engagement in East Germany - Christin Jänicke (PArtecipazione e COnflitto : PACO = PArticipation and COnflict, 2024)
More than 30 years after the end of the GDR, there is still an East-West divide in society, which is also reflected in current German antifa movements. In recent years, the perception of the East has once again become more closely associated with and shaped by the far right. Although the debate about the growth of the far right in the East is not new, we know little about its impact on antifascist resistance. In this article, I demonstrate that today's East-German Antifa finds itself in an ambivalent relationship between recognising and fighting the right-wing hegemony on the one hand, and on the other, evoking a positive reference to the East that emphasises the resistances of antifascist civil society and opposes stigmatisation. Activists evoke historical narratives and common struggles in reaction to the successes of the far right in the region and the re-emergence of homogenising media discourse surrounding the so-called `Brown East'. The latter reduces the far right to solely a problem of the eastern part of Germany. I argue that activist focus on East Germany functions primarily as a resource to counter the specific far-right movements in the region. Secondly, it serves as an empowerment intended to raise the visibility of antifascist activities, which have been rendered invisible by the discourse surrounding the `Brown East'. My findings are based on a qualitative content analysis of a public debate in Berlin's Zionskirche in 2021. The results show how shared experiences of marginalisation, othering, and derogation as East Germans can be situated within a broader discourse around the East.
Keywords: 320; antifascism; far right; hegemony; memory; social movement